1994
DOI: 10.1093/oxfordjournals.humrep.a138572
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization of human oocytes following cryopreservation; normal karyotypes and absence of stray chromosomes

Abstract: Survival following cryopreservation of fresh and aged human oocytes by the propanediol (PROH) procedure was observed in 51 and 73% of oocytes respectively, immediately after thawing. This survival was reduced in both types of oocytes at the time of insemination (3-4 h) to 41% in fresh and 61% in aged oocytes. Insemination of the cryopreserved and control oocytes with spermatozoa from one donor resulted in total fertilization rates similar to our in-vitro fertilization (IVF) rate for non-male factor patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(78 citation statements)
references
References 0 publications
4
68
0
6
Order By: Relevance
“…It has been reported that there is no increase in the rates of aneuploidy or abnormal karyotype in onecell rabbit embryos [64] and mature mouse or human oocytes [65,66] when they were treated with PROH as a cryoprotectant. However, PROH is not effective for cryopreservation of mouse and human oocytes when a slow freezing procedure is u s e d b e c a u s e o f a h i g h i n c i d e n c e o f parthenogenetic activation found after freezingthawing with 1.5 M of PROH [60,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there is no increase in the rates of aneuploidy or abnormal karyotype in onecell rabbit embryos [64] and mature mouse or human oocytes [65,66] when they were treated with PROH as a cryoprotectant. However, PROH is not effective for cryopreservation of mouse and human oocytes when a slow freezing procedure is u s e d b e c a u s e o f a h i g h i n c i d e n c e o f parthenogenetic activation found after freezingthawing with 1.5 M of PROH [60,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…The resurgence of interest in human oocyte cryopreservation as a consequence of a number of reports suggesting that it may be a safe option in appropriate circumstances [1][2][3][4] has led to its clinical application and reports of a number of live births [5][6][7][8][9][10]. Although this approach has been adopted as an adjunct to routine IVF practice in Italy, this is predominantly a consequence of legal developments which resulted in the prohibition of the alternative, and more widepread, option of embryo cryopreservation.…”
Section: Introductionmentioning
confidence: 99%
“…Early concerns regarding damage to the meiotic spindle [3], loss of cortical granules leading to lowered fertilization rates [4,5] and the low success rates of oocyte freezing/thawing as compared to the relative success of embryo cryopreservation caused a wavering of interest until the 1990s. Then, a series of studies indicating that reasonable oocyte thaw survival [6], fertilization [7,8], embryos with normal karyotype [8][9][10], and viable blastocyst development [11] could be achieved led to renewed interest in OC technology. Reports demonstrating live births following application of OC appeared soon after [12,13].…”
Section: Introductionmentioning
confidence: 99%